Vaccination of individuals lacking decision-making capacity during a public health emergency. Issue 2 (20th October 2022) - Schaefer, G Owen; Johnson, Tess; Friets, Ryan; Menon, Sumytra; Savulescu, Julian
Abstract: This paper explores the ethical challenges in deciding whether to vaccinate individuals lacking the decision-making capacity needed to provide informed consent during a public health emergency like COVID-19. The best interests standard ordinarily governs such decisions, which under the law in jurisdictions like England, Wales and Singapore takes into account the individual's past wishes and present preferences. However, in a public health emergency, the interests of third parties become more salient: those whom the unvaccinated individual might expose to infection have an interest in the individual's being vaccinated. While current mental capacity law has not been interpreted to take such public health considerations into account, we argue that such considerations are nevertheless ethically relevant, and can legitimately be weighed up alongside other considerations such as the preferences of the individual and impacts on their health. This is most relevant for individuals lacking decision-making capacity who have previously declined or presently resist vaccination. The public health impact of vaccination may in some instances be enough to outweigh preferences of the individual and justify providing vaccination against their past or present wishes.